Entrepreneurial Intention Among Children: Findings From School-Going Children Compared With Children at Workplace - Ilyas, Aamar (Animo Repository, 2023)
This research compares the entrepreneurial intention among school-going children and children at work (child labor) who are optimistic about entrepreneurship. Furthermore, we analyze the relationship between personality factors and three perceptual variables of the theory of planned behavior (TPB) with entrepreneurial intentions. We used hand-collected data techniques from school-going children and children at the workplace to investigate the proposed relationships. The in-house survey was conducted in five towns of Lahore city. The convenience sampling technique was used to collect data from 450 school-going children, and the snowball sampling technique was used to collect data from 450 child laborers. The statistical findings show that both school-going children and children at the workplace hold optimistic attitudes toward starting a new venture. During the comparison of these two datasets, we found more significant differences than similarities. However, the intentions of child laborers were more entrepreneurial than school-age children. Moreover, both school-going children and children at the workplace scored above average in three personality traits (optimism, competitiveness, and risk-taking tendency); they predicted higher entrepreneurial intention (EI). Innovativeness also predicted intention for school-going children but not for children at the workplace sample. The findings of this study were based on only one developing nation. It is not generalized to other countries due to cultural variations. In future research, data would be collected from numerous regions, developed or developing nations, improving generalizability. Furthermore, only four constructs of personality traits were used, ignoring social and contextual factors. This study provides new insights for educational policymakers and practitioners. They should develop a comprehensive policy and incorporate entrepreneurship education in our secondary schools to boost entrepreneurial knowledge. Moreover, practitioners may change effective policy reforms to foster the interest of child laborers in entrepreneurship. This study contributes to the child labor and entrepreneurship literature by comparing the entrepreneurial intention among school-going children and children at the workplace. As far as the researchers’ experience, there is no empirical evidence in the literature on this unique phenomenon.